2009
DOI: 10.1373/clinchem.2008.118000
|View full text |Cite
|
Sign up to set email alerts
|

Activity Assays and Immunoassays for Plasma Renin and Prorenin: Information Provided and Precautions Necessary for Accurate Measurement

Abstract: BACKGROUND:Measurement of plasma renin is important for the clinical assessment of hypertensive patients. The most common methods for measuring plasma renin are the plasma renin activity (PRA) assay and the renin immunoassay. The clinical application of renin inhibitor therapy has thrown into focus the differences in information provided by activity assays and immunoassays for renin and prorenin measurement and has drawn attention to the need for precautions to ensure their accurate measurement.CONTENT: Renin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
129
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(133 citation statements)
references
References 68 publications
3
129
0
1
Order By: Relevance
“…Some studies in healthy volunteers reported a close correlation between PRA values and plasma renin concentrations, as determined by immunoassay. 29 However, this correlation was not as close for low PRA and plasma renin concentrations, and in patients with different angiotensinogen concentrations. 29 The pivotal role of aldosterone in the pathophysiology of EH is now well documented.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies in healthy volunteers reported a close correlation between PRA values and plasma renin concentrations, as determined by immunoassay. 29 However, this correlation was not as close for low PRA and plasma renin concentrations, and in patients with different angiotensinogen concentrations. 29 The pivotal role of aldosterone in the pathophysiology of EH is now well documented.…”
Section: Discussionmentioning
confidence: 98%
“…29 However, this correlation was not as close for low PRA and plasma renin concentrations, and in patients with different angiotensinogen concentrations. 29 The pivotal role of aldosterone in the pathophysiology of EH is now well documented. [30][31][32] Although 15% of patients with hypertension exhibit alterations in aldosterone regulation, they do not meet the criteria for PA. Suppression of renin is thought to be the earliest feature of PA. 33 The use of A PL /PRA ratio in populations with high prevalence of low-renin hypertension may lead to a high number of false-positive results.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, in recent years automated methodology for PRC measurement has been developed. The disadvantages include greater prorenin cryoactivation effects and less sensitivity when measuring low renin concentrations (35). Since PRC and ALD/renin ratio have been proposed for PA screening (4,5), we determined PRC in a subgroup of randomly selected controls and hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, circulating renin levels were measured using the PRA assay, which is one of the most commonly used methods for measuring plasma renin. 22 In the absence of renin inhibitors or other RAAS-related antagonists, activity assays provide information regarding the quantity of enzymatically active renin in the plasma. 22 …”
Section: Clinical Measurementsmentioning
confidence: 99%
“…22 In the absence of renin inhibitors or other RAAS-related antagonists, activity assays provide information regarding the quantity of enzymatically active renin in the plasma. 22 …”
Section: Clinical Measurementsmentioning
confidence: 99%